PEMERIKSAAN FISIK, TEKANAN DARAH, GULA DARAH, DAN ASAM URAT DI PELAYANAN SOSIAL TRESNA WERDHA JOMBANG 2021 - Zuanta Pangestuti; Cikra Ikhda Nur Hamidah Safitri; Yoehania Yoehania (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Pelayanan Sosial Tresna Werdha (PSWT) Jombang is part of the East Java Provincial Social Service which provides social services for clients, namely neglected elderly (elderly) aged 60 (sixty) years and over, administration and community services. Health problems faced by the elderly in PSWT today include Rheumatic, Hypertension and Diabetes Mellitus. The implementation of community service activities is carried out to provide health check services and free treatment to maintain the health of PSWT clients. The method in this activity is to do a physical examination of the client then given treatment and counseling. The target in the implementation of this community service is PSWT clients. The result of this activity is that it is known that the client has an increase in blood sugar levels, uric acid and high blood pressure. In addition, there are clients who have had a stroke. The complaints felt by the majority of clients are back pain, knees and dizziness. The conclusion of this activity is that clients at PSTW get free health checks and treatment equally.